IDENTIFIKASI POLA SIRKULASI LINGKUNGAN KAMPUS UNIVERSITAS PENDIDIKAN INDONESIA : Penelitian terhadap sirkulasi kampus UPI - Herdiana, Dian (2014)
Indonesian Education University Campus is an area that has a circulation system and consists of a network of lines connecting roads and movement, vehicle circulation, pedestrian circulation and parking systems. On the Indonesian Education University Campus for the circulation pattern is not optimal for the movement of vehicles, pedestrians and especially for the disabled. The purpose of this study was to examine the pattern of circulation of vehicles, pedestrians and disabled in accordance with the theory of the circulation, pedestrian circulation, pedestrian circulation and circulation with disabilities. The foundation of the theory is taken on circulation, pedestrian circulation, circulation and circulation of vehicles for the disabled.The method used in this study is qualitative descriptive research. The data was collected in two (2) ways, namely direct observation and documentation directly in the field and then analyzed using content similarity and descriptive. The findings of this study is how the existing circulation patterns of two-wheeled vehicles or four wheel, pedestrian circulation patterns and circulation patterns with disabilities according to the theory. With emphasis on safety and comfort of a good circulation of users and the default size of the facility - facilities. Keywords: Circulation Patterns vehicles, pedestrians and the disabled. Kampus Universitas Pendidikan Indonesia (UPI) merupakan kawasan pendidikan yang memiliki sistem sirkulasi dan jalur penghubung terdiri dari jaringan jalan dan pergerakan, sirkulasi kendaraan, sirkulasi pejalan kaki, dan sistem parkir.Di lingkungan kampus Universitas Pendidikan Indonesia (UPI) untuk pola sirkulasinya belum optimal untuk pergerakan kendaraan, pejalan kaki dan terutama untuk difabel.Tujuan penelitian ini adalah untuk meneliti pola sirkulasi kendaraan, pejalan kaki dan difabel sesuai dengan teori tentang sirkulasi, sirkulasi pejalan kaki, sirkulasi pejalan kaki dan sirkulasi difabel.Landasan teori yang diambil yaitu tentang sirkulasi, sirkulasi pejalan kaki, sirkulasi kendaraan dan sirkulasi untuk difabel.Metode yang digunakan dalam penelitian ini adalah jenis penelitian deskriptif kualitatif. Data penelitian ini dikumpulkan dalam 2 (dua) cara, yaitu observasi langsung dan dokumentasi langsung di lapangan dan selanjutnya dianalisis dengan menggunakan kesamaan isi dan deskriptif. Temuan penelitian ini adalah bagaimana existing pola sirkulasi kendaraan roda dua maupun roda empat, pola sirkulasi pejalan kaki dan pola sirkulasi difabel sesuai pada teori.Dengan mengutamakan keamanan dan kenyaman pengguna sirkulasi baik dari ukuran standarnya maupun dari fasilitas - fasilitas pendukungnya. Kata Kunci : Pola Sirkulasi Kendaraan, pejalan kaki dan difabel.